Dynamics of Multiculturalism and Religious Pluralism: Strategies for Building Social Cohesion in Indonesia - Mawardi, Kholid (Asian Journal of Philosophy and Religion, 2024)
This study explores the intricate relationship between religion and multiculturalism in Indonesia, a nation marked by its rich cultural diversity and complex religious dynamics. The research aims to examine how these factors contribute to societal harmony or conflict. Utilizing a qualitative approach, this study conducts a literature analysis, drawing from a wide range of scholarly sources on religion, multiculturalism, and interfaith harmony in the Indonesian context. The findings indicate that while multiculturalism and religious pluralism offer frameworks for coexistence, challenges persist due to historical tensions and socio-political factors. The analysis highlights the role of perception in conflict dynamics, emphasizing that differences in communication styles, ethical norms, and religious beliefs can escalate tensions. Conversely, effective interfaith dialogue and inclusive policies can promote harmony. The study concludes that fostering a deeper understanding of multiculturalism and an inclusive approach to religion is crucial for reducing conflicts and enhancing societal cohesion. Addressing underlying socio-economic and political factors is essential for sustainable peace and unity in Indonesia.